Inflammation and nodavirus encephalopathy in turbot (Scophthalmus maximus) - Montes, Ariana; Figueras Huerta, Antonio; Novoa, Beatriz (2009)
Poster.-- 14th EAFP International conference on diseases of fish and shellfish, Prague, 14-19 September 2009 No